Africa’s digital solutions to tackle COVID-19 - European Investment Bank (European Investment Bank, 2021)
African countries are using technology in many new ways to fight the coronavirus pandemic. This report highlights some of the best digital solutions and estimates the investments required to implement the technology on a wider scale. The European Investment Bank prepared this report with the support of the United Nations Development Programme and the consulting firm BearingPoint.